La demanda externa de quinua y su incidencia en el nivel de exportaciones agropecuarias no tradicionales peruanas, período: 2004-2014. - Rojas Quiroz, Anderson Michael (2016)
This research has as main objective to analyze the evolution of external demand for quinoa and its impact on the level of Peruvian non-traditional agricultural exports during the period: 2004-2014. The importance of this research is that it gives an idea of what is significant or not it can be external demand for quinoa on the level of Peruvian exports of non-traditional agricultural sector. This paper poses the following problem What is the impact external demand for quinoa in the level of non-traditional agricultural exports, period: 2004 - 2014? The assumption made is that foreign demand for quinoa has impacted significantly on the level of domestic exports of non-traditional agricultural sector during the period 2004-2014. This research is not an experimental basis, to develop a statistical sources that have provided data for later analysis throughout the study period was used. It is concluded that foreign demand for quinoa has shown to have an increasing impact on the level of non-traditional agricultural exports in Peru.